Sociodemographic Predictors of Satisfaction with Life among Students from Public Educational Institutions at Arequipa City - Arias Gallegos, Walter Lizandro (2019)
This study analyzes some sociodemographic factors, which could predict the satisfaction with life in a sample of high school students from Arequipa, following the theoretical frame of the Positive Psychology. We tested a sample of 872 students of 4th and 5th grade, from five public local high schools, who were 46.9 % males and 53.1 % females. A sociodemographic chart and the Satisfaction with Life Scale were applied, in the version validated to Arequipa City (Arias, Huamani, & Caycho-Rodríguez, 2018). The data was processed by structural equations modeling. The results indicate that sex and school have some predictive power over life satisfaction.